Policy selection of knowledge: The changing network of experts in the development of an emission trading scheme. Issue 106 (November 2019) - Lo, Alex Y.; Chen, Kang
Highlights: This article traces the development of a Chinese emission trading scheme. It shows how the role, membership, and structure of an expert network change over time. Earlier processes required elite learning and closed interactions among actors. Later processes enabled broad-base participation and privileged practice-based knowledge. Findings inform discussions on the organization of knowledge-based networks and institutions. Abstract: Knowledge-based experts contribute to climate change policy change. However, the issue of how the role, membership, and structure of expert networks change over a policy cycle remains poorly explained, undermining the case for recognizing a dynamic and inclusive evidence base containing power. This article traces the development of a Chinese emission trading scheme and analyses the changing conditions for knowledge production, acquisition and delivery to shed light on governance. In-depth interviews with 62 experts and other actors were conducted and analyzed using a framework comprising three policy sub-processes, three drivers of change, and five groups of actors. Between 2012 and 2017, the emission trading scheme experienced three stages of development. The initial planning process utilized strategic, system-level inputs from elite experts, learning from applied research and international experience. Emerging priorities arising from policy implementation and diffusion strengthened the role of those who are well versed in the practice and/or industry and enabled broad-base participation. The study enhances our understanding of expert involvement as a continuous, dynamic, and adaptive process amenable to the developmental needs of policy. Findings can inform discussions on the implications of shifting policy priorities and needs for knowledge-producing organizations and for broadening the evidence base of policy.